Impact of telecommuting on employee well-being: the role of job demands, job resources and psychological capital - Delhaas, Lodewijk Onno (2021)
Al though organisations are increasingly implementing telecommuting as a new flexible work design, consensus on the consequences for employee well-being is missing. Therefore, using the Job Demands-Resources(JD-R)model as a conceptual basis, this study investigated the impact of the extent of telecommuting on work exhaustion and work engagement. Additionally, to fully grasp the underlying mechanisms governing these effects, this study also analysed the potential mediating process of job characteristics (i.e., job demands and job resources)in the link between telecommuting and employee well-being, the potential moderating impact of personal resources in the form of psychological capital(Psy Cap) on perceived job characteristics, as well as the potential moderating role of job resources in the relationship between job demands and work exhaustion. Cross-sectional data were collected from 123 individuals of various organisations working in a telecommuting setting. Results indicated that telecommuting did not directly affect work exhaustion nor work engagement but revealed that it main lyhad adverse consequences for perceived job characteristics. Regarding individual differences, it was shown that Psy Cap both had a buffering and exacerbating effect on experienced job characteristics. Similar counter directions were established for the moderating effects of job resources on the job demands-work exhaustion relationship. This study contributes to literature by demonstrating the importance of having a holistic overview of both job and individual characteristics when analysing the development of occupational well-being in a telecommuting environment.